Admission Practices of National Open University of Nigeria (NOUN): A Solution to the Challenges of Education Access in Nigeria - Bappah, Adamu (West African Journal of Open and Flexible Learning, 2018)
The study investigated the admission Practices of the National Open University of Nigeria (NOUN) in addressing the challenges of access, gender equity and promotion of federal character principle. The study population comprised 1425 academic and non-academic staff of NOUN in which 6 samples were purposely selected from the population. Interview protocol and documents were used for data collection. The study adopted a qualitative research approach using case study design. Data analysis involved thematic and content analysis via computer assisted software Nvivo 11. The results obtained indicated admission practices of NOUN were a combination of merit based, open access and computerized system of admission which made it possible for every applicant to be admitted without barrier. The result also revealed that although the practice of admission in NOUN had all that is required to address the challenge of access to university education, fear of acceptance, cost, technophobia and lack of awareness were the major reasons that impeded on access to NOUN. The findings also revealed that admission practices of NOUN addressed the challenges of gender equity in accessing university education by democratizing access to education, providing equal access opportunity to applicants and giving freedom to those restricted due to social conditions and the practices also circumvented geographical, religious and ethnic barriers, the process properly reflected the doctrine of federal character principle. The study recommends that Government should empower the institution to operate to it full capacity so that its vision will be fully realized. NOUN, Government and other stake holders should embark on massive sensitization to educate the public on the operation of the university and candidates who have lost out in the admission process of conventional universities should be encourage to apply in NOUN instead of wasting so many years trying to pursue admission in conventional Universities. Résumé : L'article a étudié les pratiques d'admission de l’Université Nationale Ouverte du Nigeria (NOUN) pour relever les défis de l'accès, de l'équité entre les sexes et de la promotion du principe de caractère fédéral. La population étudiée comprend 1425 membres du personnel académique et non académique de NOUN, dans lesquels 6 échantillons ont été choisis à dessein parmi la population. Le protocole d'entrevue et les documents ont été utilisés pour la collecte de données. L'étude a adopté une approche de recherche qualitative utilisant la conception instrumentale d'étude de cas. L'analyse des données implique l'analyse thématique et de contenu via le logiciel assisté par ordinateur Nvivo 11. Les résultats obtenus indiquent que les pratiques d'admission de NOUN sont une combinaison de systèmes d'admission fondés sur le mérite, d'accès libre et d'informatisation qui a permis à chaque demandeur d'être admis sans obstacle. Le résultat a également révélé que, bien que la pratique de l'admission à NOUN ait tout ce qu'il faut pour relever le défi de l'accès à l'enseignement universitaire, la peur de l'acceptation, le coût, la technophobie et le manque de sensibilisation sont les principales raisons qui empêchaient l'accès à NOUN. Les résultats ont également révélé que les pratiques d'admission de NOUN ont abordé les défis de l'équité entre les sexes dans l'accès à l'enseignement universitaire en démocratisant l'accès à l'éducation, en offrant des chances d'accès égal aux candidats et en donnant la liberté à ceux qui sont exclus en raison des conditions sociales et en contournant également les barrières géographiques, religieuses et ethniques. Le processus reflète correctement la doctrine du principe de caractère fédéral. L'étude recommande que le gouvernement donne à l'institution les moyens de fonctionner à pleine capacité afin que sa vision soit pleinement réalisée. NOUN, le gouvernement et d'autres acteurs devraient se lancer dans une sensibilisation massive pour éduquer le public sur le fonctionnement de l'université et les candidats qui ont perdu dans le processus d'admission des universités conventionnelles devraient être encouragés à postuler à NOUN au lieu de gaspiller tant d'années à essayer de poursuivre l'admission dans les universités conventionnelles.